Potent antitumor activity of ensartinib in MET exon 14 skipping-mutated non-small cell lung cancer. (1st May 2023) - Xia, Yang; Jin, Rui; Li, Miao; Lan, Fen; Zhu, Hao; Yu, Yinghui; Miao, Da; Wang, Qiyuan; Zhou, Yi; Selvaggi, Giovanni; Ying, Songmin; Zhang, Jianjun; et al.
Abstract: Met proto-oncogene exon 14 skipping ( MET ex14) mutations are targetable driver genes in approximately 3% of non-small-cell lung cancers (NSCLCs). Ensartinib, a type Ia MET inhibitor, is a multi-kinase inhibitor that has been approved for ALK -positive NSCLCs. Ensartinib was administered for compassionate use (cohort 1) and in a phase II clinical trial (cohort 2) to patients with MET ex14 mutant NSCLCs, with ORR as a primary endpoint. Molecular simulation was conducted to evaluate ensartinib c-MET interaction, and cell lines, patient-derived organoids (PDOs), and xenograft models were used to test the effectiveness of ensartinib. Among 29 evaluable patients, the ORR and DCR of ensartinib were 67% and 94% in cohort 1, and 73% and 91% in cohort 2. The median DoR was 6.8 months and median PFS was 6.1 months in the total population. Rash was the most common drug-related adverse event, and peripheral edema of any grade was reported in only 9% patients. Molecular simulations indicated favorable binding of ensartinib to c-MET. The kinase assay demonstrated an IC50 of 7.9 nM of ensartinib against MET ex14 protein. In vitro, Hs746T ( MET ex14 mutation) and EBC-1 ( MET amplification) cells were sensitive to ensartinib, with IC50 values of 31 and 44 nM, respectively. Ensartinib exhibited comparable inhibitory effects on cell migration as crizotinib and tepotinib in both cell types. In vivo, ensartinib suppressed the growth of Hs746T cells. Ensartinib also potently inhibited the viability of PDOs. Overall, Ensartinib exhibited substantial antitumor effects against MET ex14 mutant NSCLCs in preclinical and clinical trials, with relatively low peripheral edema rates. Highlights: Ensartinib confers potent efficacy against MET  exon 14 skipping mutant NSCLC. Rash rather than peripheral edema emerges as the most common AE for ensartinib. Ensartinib exhibits strong anti-MET effects both in vitro and in vivo.